2019
DOI: 10.5267/j.msl.2019.7.001
|View full text |Cite
|
Sign up to set email alerts
|

A study of the factors affecting the content created by international travellers in Vietnam

Abstract: Nowadays, international visitors often use the Internet to find information and share their travel experiences on social networks. This action helps other travellers make their traveling plans easier. However, there has not been much research on the user's perception on the use of travel content. This study aims to develop a model to measure the impact of user's perception on user-generated tourism content and to use the SEM model to test the feasibility of the proposed model. Results show that the perceived u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…As other service industries, the aviation industry has been forced to generated competitive advantages among global competition. Clients' expectation continuously increases day by day and subsequent demands for improving service quality (Lin et al, 2009;Chou et al, 2011;Kim and Lee, 2011;Anh et al, 2019;Allahham, 2013). Competitive advantage of any airlines is to deliver superior service quality.…”
Section: Introductionmentioning
confidence: 99%
“…As other service industries, the aviation industry has been forced to generated competitive advantages among global competition. Clients' expectation continuously increases day by day and subsequent demands for improving service quality (Lin et al, 2009;Chou et al, 2011;Kim and Lee, 2011;Anh et al, 2019;Allahham, 2013). Competitive advantage of any airlines is to deliver superior service quality.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the exchange rate maintained a positive effect on the demand of foreign tourists. Anh et al (2019) developed a model to measure the effect of user's perception on user-generated tourism content and reported that that the perceived usefulness indirectly influenced user-generated content through electronic word of mouth (eWOM), attitudes of visitors when choosing destinations and attitudes when implementing media social communication. Tran et al (2019) measured the level of economic linkage in key economic zones in central Vietnam generally and measured the effect of economic linkage in the tourism sector.…”
Section: Introductionmentioning
confidence: 99%